Modifikasi Natrium Alginat dengan Metode Oksidasi Periodat - Wilandani Sabilla; Arlina Prima Putri; Farendina Suarantika (UNISBA Press, 2024)
Abstract. This research aims to modify sodium alginate using the periodate oxidation method. The alginate used is not easily biodegradable, so oxidation is carried out with sodium metaperiodate to facilitate biodegradation and produce new functional groups. With the presence of new functional groups in alginate, hydrogels can be formed using type B gelatin and BaCl2. Alginate was successfully synthesized because an oxidation degree of 3% was obtained and the Fourier Transform Infra Red Attenuated Total Reflectance (FTIR-ATR) results showed a band of 1720 cm-1 which indicated a change in alginate to Alginate Dialdehyde (ADA). Abstrak. Penelitian ini bertujuan untuk modifikasi natrium alginat dengan metode oksidasi periodat. Alginat yang digunakan tidak mudah terbiodegradasi, sehingga dilakukan oksidasi dengan natrium metaperiodat untuk mempermudah biodegradasi dan menghasilkan gugus fungsi baru. Dengan adanya gugus fungsi baru pada alginat maka hidrogel dapat dibentuk dengan menggunakan gelatin tipe B dan BaCl2. Alginat berhasil disintesis karena diperoleh derajat oksidasi 3% dan hasil Fourier Transform Infra Red Attenuated Total Reflectance (FTIR-ATR) menunjukkan pita 1720 cm-1 yang menunjukkan adanya perubahan alginat menjadi Alginat Dialdehida (ADA).